Advancements in end treatment techniques and applications of acid mine drainage in coal mines: A research review - Qiaohui CHE; Song DU; Degao ZHANG; Yinglin FAN; Xiao ZHANG; Fengli WANG (Meitan kexue jishu)
Acid mine drainage(AMD) from coal mines contains elevated concentrations of heavy metals and sulfates, rendering it highly corrosive and posing a persistent threat to both the ecological environment and human health. Consequently, it has emerged as a pervasive environmental predicament in the coal mining process. This review presents an overview of the formation mechanism, detrimental effects, and chemical characteristics of AMD in coal mines. Furthermore, it summarizes traditional AMD end treatment methods in recent years, analyzes and compares practical application cases of AMD end treatment in China, and introduces emerging AMD end treatment methods. The reaction mechanisms, advantages, disadvantages of traditional active treatments (neutralization, adsorption, membrane technology), as well as passive treatments (constructed wetlands, limestone ditch drainage), are discussed extensively. Moreover, the applicability of each treatment method is evaluated. However, these methods still have certain limitations. The active method is constrained by the continuous supply of chemicals and energy as well as high maintenance costs. On the other hand, the passive approach is limited by long treatment cycles and the need for timely system renovation. According to the actual application cases, the treatment ideas and optimization methods of domestic AMD end treatment methods are summarized. In order to address these challenges in acid mine drainage treatment within coal mines, this review introduces magnetic nanoparticle materials and a novel collaborative treatment method, providing a fresh perspective. The findings of this study highlight the ongoing necessity to enhance existing technologies and develop new ones to improve the overall effectiveness of acid mine drainage treatment. Relying solely on a single technology proves difficult in meeting discharge standards for acid mine drainage treatment; therefore, adopting a multi-technology collaborative approach based on complementary advantages becomes imperative. Furthermore, during the process of AMD treatment，the approach of “source reduction + end treatment” can be adopted to improve the effectiveness of AMD treatment, resource recovery and reuse can help reduce treatment costs while promoting sustainable management.